Aegle marmelos Extract Can Enhance Memory in Rats: Effect of Aegle marmelos extract on learning and memory - Amir Farshchi; Golbarg Ghiasi; Samira Ghiasi (Iranian Journal of Pharmaceutical Sciences, 2010)
Diabetes mellitus is associated with disturbances of learning and memory and cognitive functioning. Aegle marmelos Corr. from Rutaceae family, is widely used in Iranian folk medicine for the treatment of diabetes mellitus. It decreases blood glucose level by improving glucose tolerance and also has lipid-lowering and antioxidant properties. Considering the beneficial antidiabetic potential of A. marmelos, this study was conducted to evaluate the effect of chronic oral administration of A. marmelos as cognitive enhancer, on learning and spatial memory in diabetic rats using Morris water maze test. Male Wistar rats were randomly divided into normal-control, diabetic-control, and A. marmelos-treated diabetic groups (100, 250 and 500 mg/kg, p.o., 4 weeks). Diabetes was induced by a single dose i.p. injection of streptozotocin (45 mg/kg). In each group of animals, spatial learning and memory parameters were analyzed. A. marmelos showed dose dependent improvement in spatial learning and memory parameters. Swimming time (Escape Latency) in normal-control and A. marmelos-treated diabetic animals rats was significantly lower than diabetic-control, while swimming speed was significantly higher. The study demonstrated that A. marmelos has a significant protective effect against diabetes-induced spatial learning and memory deficits. This effect can be attributed to hypoglycemic, hypolipidemic and antioxidant activity of A. marmelos.